Karakteristik Angin Monsun Barat pada Periode Puncak Musim Hujan di Bandar Udara Sultan Hasanuddin Makassar - Richard, Richard; Jasruddin, Jasruddin; Arsyad, Muhammad; Prasetyo, Adi (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2025)
This study aims to examine the characteristics of the West Monsoon wind based on convergence values at Sultan Hasanuddin International Airport, wind disturbance patterns over the Java Sea, the source and speed of air masses, regional-scale wind disturbances over Indonesia (Tropical Cyclones and Eddies), and wind flow patterns entering the study area under different rainfall categories during the period 2014 – 2023. The research employed a quantitative method by processing rainfall data and daily zonal (u) and meridional (v) wind component data during the peak rainy season (December – February). The analysis was conducted using the GrADS application to display streamline maps, data processing with Excel, and descriptive analysis. The results indicate that for the no-rain to light-rain categories, the characteristics of the West Monsoon wind are not clearly evident, except for wind disturbance patterns over the Java Sea and the speed and consistency of winds from the air-mass source toward the study area. In contrast, for moderate to very heavy or extreme rainfall categories, the characteristics of the West Monsoon wind are clearly observed. These conditions are characterized by air masses originating from the South China Sea, supported by strong and consistent wind speeds passing through the Karimata Strait and the Java Sea to Sultan Hasanuddin International Airport, as well as the presence of wind disturbances in the form of moderate to strong convergence over the Java Sea extending to the Makassar region. Therefore, the study concludes that the no-rain and light-rain categories exhibit nearly similar wind characteristics, while the main differences in the moderate to extreme rainfall categories lie in the consistency of wind speed and the intensity of convergence over the Java Sea.